Potential risk factors associated with human alveolar echinococcosis: Systematic review and meta-analysis. - Franz J Conraths; Carolina Probst; Alessia Possenti; Belgees Boufana; Rosella Saulle; Giuseppe La Torre; Luca Busani; Adriano Casulli (Public Library of Science (PLoS), 2017)
Human alveolar echinococcosis (AE) is a severe zoonotic disease caused by the metacestode stage of Echinococcus multilocularis. AE is commonly associated with a long incubation period that may last for more than ten years. The objective of this systematic literature review was to identify and summarize the current knowledge on statistically relevant potential risk factors (PRFs) associated with AE in humans.Six bibliographic databases were searched, generating a total of 1,009 publications. Following the removal of duplicate records and the exclusion of papers that failed to meet the criteria of a previously agreed a priori protocol, 23 publications were retained; however, 6 of these did not contain data in a format that allowed their inclusion in the meta-analysis. The remaining 17 publications (6 case-control and 11 cross-sectional studies) were meta-analysed to investigate associations between AE and PRFs. Pooled odds ratios (OR) were used as a measure of effect and separately analysed for case-control and cross-sectional studies. In the case-control studies, the following PRFs for human AE showed higher odds of outcome: "dog ownership", "cat ownership", "have a kitchen garden", "occupation: farmer", "haymaking in meadows not adjacent to water", "went to forests for vocational reasons", "chewed grass" and "hunting / handling foxes". In the cross-sectional studies, the following PRFs showed higher odds of outcome: "dog ownership", "play with dogs", "gender: female", "age over 20 years", "ethnic group: Tibetan", "low income", "source of drinking water other than well or tap", "occupation: herding" and "low education". Our meta-analysis confirmed that the chance of AE transmission through ingestion of food and water contaminated with E. multilocularis eggs exists, but showed also that food- and water-borne PRFs do not significantly increase the risk of infection.This systematic review analysed international peer-reviewed articles that have over the years contributed to our current understanding of the epidemiology of human AE. The identification of potential risk factors may help researchers and decision makers improve surveillance and/or preventive measures that aim at decreasing human infection with E. multilocularis. More primary studies are needed to confirm potential risk factors and their role in the epidemiology of human AE.